2021
DOI: 10.1111/odi.13963
|View full text |Cite
|
Sign up to set email alerts
|

Acquired oral syphilis: A multicenter study of 339 patients from South America

Abstract: Objective To report the clinicopathologic features of acquired oral syphilis cases in South American countries. Materials and Methods Clinical data were retrospectively collected from the records of 18 oral diagnostic services in Argentina, Brazil, Chile, Colombia, Venezuela, Uruguay, and Peru. Serologies of nontreponemal and treponemal tests were used for diagnosis. Results The series comprised 339 cases of acquired oral syphilis. Secondary syphilis ranked as the most common stage (86.7%). Lesions were more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
2
20
2
Order By: Relevance
“…It is generally accepted that more males are diagnosed with syphilis than females [4], [6], [31], [114], [115] with a peak in the third and fourth decades of life (age groups 20-29 years and 30-39 years). The mean age of males is also higher as compared to that of females [4], [6], [31], [114], [115]. A case series from the files of [4] included 24 males (60%, mean age 36.4 years) and 16 (40%, mean age 35.3 years) females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that more males are diagnosed with syphilis than females [4], [6], [31], [114], [115] with a peak in the third and fourth decades of life (age groups 20-29 years and 30-39 years). The mean age of males is also higher as compared to that of females [4], [6], [31], [114], [115]. A case series from the files of [4] included 24 males (60%, mean age 36.4 years) and 16 (40%, mean age 35.3 years) females.…”
Section: Discussionmentioning
confidence: 99%
“…In their retrospective study, [6] mainly described oral lesions as single (96.5%) ulcerations (79%), and that those lesions usually presented as mucosal plaques when they appeared at multiple sites (p < 0.05). Another retrospective study by de [115] reported that acquired oral syphilis usually presented as mucous patches (28.4%), papules (25.7%) or ulcers (18.1%). A single anatomical site was involved in 87% cases of primary syphilis, while 50.5% of the cases involved one anatomical site, 21% affected two sites, and 8% affected three or more sites in cases of secondary syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…4 While much consideration has been given to the high rates among men and a large proportion of cases affecting men who have sex with men (MSM), especially those HIV-positive, increased trends among women have also been highlighted. 5,6 However, risk factors associated with the disease are barely explored in studies reporting cases of individuals with AOS. Recently, we reported 339 cases of AOS identified at 18 referral services from seven South American countries.…”
mentioning
confidence: 99%
“…Recently, we reported 339 cases of AOS identified at 18 referral services from seven South American countries. 6 Of note, information regarding risk factors was available in only 25% of cases (e.g. drug abuse, whether the individual had multiple sexual partners, and whether the individual was a sex worker or an MSM) in the records, even being the study a retrospective analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation